Psychedelic drug abuse potential assessment research for new drug applications and Controlled Substances Act scheduling. (1st November 2022) - Henningfield, Jack E.; Coe, Marion A.; Griffiths, Roland R.; Belouin, Sean J.; Berger, Ann; Coker, Allison R.; Comer, Sandra D.; Heal, David J.; Hendricks, Peter S.; Nichols, Charles D.; Sapienza, Frank; Vocci, Frank J.; et al.
Abstract: New medicines containing classic hallucinogenic and entactogenic psychedelic substance are under development for various psychiatric and neurological disorders. Many of these, including psilocybin, lysergic acid diethylamide (LSD), and 3, 4-methylenedioxymethamphetamine (MDMA) are Schedule I controlled substances of the United States Controlled Substances Act (US CSA), and similarly controlled globally. The implications of the CSA for research and medicines development, the path to approval of medicines, and their subsequent removal from Schedule I in the US are discussed. This entire process occurs within the framework of the CSA in the US and its counterparts internationally in accordance with international drug control treaties. Abuse potential related research in the US informs the eight factors of the CSA which provide the basis for rescheduling actions that must occur upon approval of a drug that contains a Schedule I substance. Abuse-related research also informs drug product labeling and the risk evaluation and mitigation strategies (REMS) will likely be required for approved medicines. Human abuse potential studies typically employed in CNS drug development may be problematic for substances with strong hallucinogenic effects such as psilocybin, and alternative strategies are discussed. Implications for research, medicinal development, and controlled substance scheduling are presented in the context of the US CSA and FDA requirements with implications for global regulation. We also discuss how abuse-related research can contribute to understanding mechanisms of action and therapeutic effects as well as the totality of the effects of the drugs on the brain, behavior, mood, and the constructs of spirituality and consciousness. Highlights for our paper: Clinical psychedelic drug research poses novel safety and scientific validity issues. The Controlled Substances Act restricts and guides psychedelic medicine research. Abuse potential assessment considers pharmacology, medical, and public health factors. Abuse potential assessment of psychedelics must inform the 8 factor assessment. Spirituality and mysticism instruments may contribute to psychedelic abuse assessment.